Two-dimensional multiplicity fluctuation analysis of target residues in nuclear collisions - 张东海 牛耀婕 王立春 闫文君 高丽娟 李明星 武丽萍 李惠玲 李俊生 (Chinese physics B, 2010)
Multiplicity fluctuation of the target residues emitted in the interactions in a wide range of projectile energies from 500 A MeV to 60 A GeV is investigated in the framework of two-dimensional scaled factorial moment methodology. The evidence of non-statistical multiplicity fluctuation is found in 160-AgBr collisions at 60 A GeV, but not in 56Fe-AgBr collisions at 500 A MeV, 84Kr-AgBr collisions at 1.7 A GeV, 16O-AgBr collisions at 3.7 A GeV and 197Au-AgBr collisions at 10.7 A GeV.